2019
DOI: 10.1016/j.aim.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Diederich–Fornæss index II: For domains of trivial index

Abstract: We study bounded pseudoconvex domains in complex Euclidean spaces. We find analytical necessary conditions and geometric sufficient conditions for a domain being of trivial Diederich-Fornaess index (i.e. the index equals to 1). We also connect a differential equation to the index. This reveals how a topological condition affects the solution of the associated differential equation and consequently obstructs the index being trivial. The proofs relies on a new method of study of the complex geometry of the bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A similar problem was considered by Liu [10], [11]. Recall that a Diederich-Fornaess exponent of Ω ⊂⊂ C n is a number η ∈ (0, 1] for which there exists a smooth defining function ρ such that −(−ρ) η is strictly plurisubharmonic.…”
Section: Introductionmentioning
confidence: 94%
“…A similar problem was considered by Liu [10], [11]. Recall that a Diederich-Fornaess exponent of Ω ⊂⊂ C n is a number η ∈ (0, 1] for which there exists a smooth defining function ρ such that −(−ρ) η is strictly plurisubharmonic.…”
Section: Introductionmentioning
confidence: 94%
“…The β-worm domains are of nontrivial index (see Diederich-Fornaess [24] and Liu [35]) and the strongly pseudoconvex domains are of trivial index. The Diederich-Fornaess index has been intensely studied by Adachi [2], Adachi-Brinkschulte [3], Harrington [27], Abdulsahib-Harrington [1], Krantz-Liu-Peloso [34], and Liu [37], [35], [36].…”
Section: Introductionmentioning
confidence: 99%
“…Looking at both global regularities and the Diederich-Fornaess index, there are many pieces of evidence indicating the global regularities and trivial index happens simultaneously (compare [12] [9] with [35] [36]), it is of interest to find a direct relation between the Diederich-Fornaess index and the regularities. However, it turns out this problem is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kohn [16] showed that if the Diederich-Fornaess index is 1 then the ∂-Neumann operator is globally regular. For more general necessary condition needed for domains to have index 1 see [18]. In general, plurisubharmonic defining functions are of importance in the study of the ∂-Neumann operator as it is a sufficient condition for global regularity of ∂-Neumann operator and the Bergman projection [2], [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%